2012
DOI: 10.11113/jt.v50.178
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Of Empty Palm Fruit Bunch For Lignin Degradation

Abstract: Potensi bagi tiga kaedah prarawatan kimia terhadap degradasi lignin tandan kelapa sawit kosong (EPFB) telah dikaji. Pada kaedah pertama, natrium hidroksida (NaOH) dan kalsium hidroksida (Ca(OH)2) digunakan secara keseluruhan sebagai agen degradasi. Pada kaedah kedua, hidrogen peroksida (H2O2) ditambah serentak bersama alkali manakala untuk kaedah ketiga H2O2 ditambah berturutan ke dalam campuran EPFB–alkali selepas 24 jam. Peratus degradasi lignin adalah 65%, 72% dan 99% menggunakan NaOH manakala 9%, 31% dan 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Philippoussis (2009) found that SD contains 37.7-49.5% cellulose, 10.7-25.0% hemicelluloses, and 26.1-29.5% Hemicellulose is a polysaccharide with a lower molecular weight than cellulose. The structural complexity of lignin, with its high molecular weight and insolubility, make its degradation difficult (Misson et al, 2009). This is reflected by the lowest mycelial growth rate in PS+EFB (25:75).…”
Section: Resultsmentioning
confidence: 99%
“…Philippoussis (2009) found that SD contains 37.7-49.5% cellulose, 10.7-25.0% hemicelluloses, and 26.1-29.5% Hemicellulose is a polysaccharide with a lower molecular weight than cellulose. The structural complexity of lignin, with its high molecular weight and insolubility, make its degradation difficult (Misson et al, 2009). This is reflected by the lowest mycelial growth rate in PS+EFB (25:75).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, peracetic acid solution has an ability to maintain hemicellulose content on the biomass, therefore the loss of hemicellulose can be reduced (Palamae et al 2014). Moreover, the selection of alkaline peroxide as the pretreatment agent was done as it removes almost all lignin content on the biomass (Misson et al 2009). Alkaline peroxide pretreatment can also improve the performance of enzymatic hydrolysis, since it plays a role in lignin release from the lignocellulose matrix and increases the degree of hydration of the cellulose (Gould 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have succeeded in achieving the delignification of EFB by using chemical treatment. It has been delignified simultaneously and consecutively by using NaOH and H2O2, with lignin removal of 72% and 99% (Misson et al, 2009). Another chemical treatment has been attempted using peracetic acid solution.…”
Section: Introductionmentioning
confidence: 99%